2006
DOI: 10.1007/s10681-006-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

The cost of participatory barley breeding

Abstract: Farmer participation in agricultural research is increasingly seen as a powerful methodology to increase the relevance of technologies developed to benefit farmers' communities. In plant breeding, farmer participation is considered as a way to increase the probability of adoption of new varieties. However, the higher expected cost of participatory plant breeding (PPB) is seen as one of the main obstacles to its wider adoption.This paper addresses the issue of the different costs to an Institution of running a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Incorporation of farmers’ opinion in breeding various crops as a way of encouraging variety adoption is becoming increasingly popular and effective in terms of cost and transferring the right varieties and technology to farmers. Mangione et al. (2006) reported no significant differences in overall costs between PPB and non‐PPB of barley at ICARDA.…”
Section: Introductionmentioning
confidence: 93%
“…Incorporation of farmers’ opinion in breeding various crops as a way of encouraging variety adoption is becoming increasingly popular and effective in terms of cost and transferring the right varieties and technology to farmers. Mangione et al. (2006) reported no significant differences in overall costs between PPB and non‐PPB of barley at ICARDA.…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, testing a large number of genotypes on-farm can be difficult (Mangione et al, 2006) and must match both farmers' time and land availability and researchers' logistical capacity. Thus, simple and robust multiple environment trial designs for on-farm progeny yield testing in the early-generation are needed to achieve gains that would exceed those of FPB programs (Atlin et al, 2001;Bänziger and Cooper, 2001).…”
mentioning
confidence: 99%
“…However, green revolution has not improved wheat production in marginal areas of the world having resource poor farmers (Sthapit et al, 1996). In order to address the problems of resource poor farmers, farmer participatory approaches were advocated by many workers (Farrington and Martin, 1988;Sthapit et al, 1994;Josi and Witcombe, 1996; Witcombe, 1996;Witcombe et al, 2003;Weltzien et al, 2003;Ashby and Lilja, 2004;Morris and Bellon, 2004;Ceccarelli and Grando, 2005;Mangione et al, 2006;Sharma and Duveiller, 2006) in selection and breeding programs. In centralized breeding system, a number of advanced breeding lines are tested and selected under research station conditions that may not resemble the environmental conditions where the lines will be subsequently grown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, being more representative (involving more farmers and a range of environmental conditions), the participatory trials produce biological and agronomic data of better quality than the on farm formal trials (Mangione et al, 2006). Smith et al (2001) found that a collaborative participatory maize selection on the farm with the lowest yield potential presented greater yield advantage than the selection on experimental station.…”
Section: Discussionmentioning
confidence: 99%